Konsep Pidana Rehabilitasi Berbasis Teori Keadilan Bermartabat bagi Pecandu dan Korban Penyalahgunaan Narkotika - Kristiani, Destalia (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
The concept of criminal rehabilitation is based on the theory of dignified justice for addicts and victims of narcotics abuse. This study aimed to analyze the implementation of law enforcement and the concept of rehabilitation arrangements based on the theory of dignified justice for addicts and victims of narcotics abuse. This study used a type of normative juridical research with a statutory approach. The data sources in this study used primary and secondary legal materials—data collection techniques using literature study and analyzed using descriptive techniques. The study results showed that the implementation of law enforcement against addicts and victims of narcotics abuse was regulated in Law Number 35 of 2009, which adheres to the rehabilitation justice system and criminal justice. The concept of regulating the rehabilitation of addicts and victims of narcotics abuse was a form of reform of the national criminal law. This update showed the existence of legal policy so that addicts and victims of narcotics abuse were expected not to repeat the crime in the future. Narcotics addicts, based on the theory of dignified justice, were victims who needed physical and psychological treatment.